Did Silesia constitute an economic region between the 13th and the 15th centuries? A survey of region-integrating and region-disintegrating economic factors - Myśliwski, Grzegorz (Wydawnictwo eBooki.com.pl, 2013)
This article constitutes an attempt at answering the question of whether Silesia, aside from being a distinct historical region, was also a distinct economic region. The author starts with Robert E. Dickinson’s theory of economic regions, the basic assumptions of which are shared by contemporary researchers of regional economies. Economic resources, the similar economic policies of Silesian rulers in the 13th and 14th centuries, high levels of urbanization in comparison to neighbouring regions and the centralizing capacity of Wrocław are considered to be the forces which bound together Silesian as an economic region. Factors retarding the economic cohesion of Silesia were analyzed as well. Those included natural disasters, invasions, internal strife, criminal activity along trade routes and a crisis in the mining industry beginning in the middle of the 14th century. Beginning with the final years of the 13th century, Silesia stabilized as an economic region containing Upper Silesia, Lower Silesia and Opava. This was not, however, a perfect cohesion, as Lower Silesia was economically superior to the other regions, which themselves had strong ties to Lesser Poland. Despite that, the crisis that took place from about 1350 until 1450 did not break the economic bonds between these three constituent elements of Silesia. In comparison to every historical and economic region on its borders, Silesia was distinguished by its advanced gold mining industry, the export of a red dyeing agent (marzanna) as well as the highest number of cities with a populations of between 3,000 and 14,000. Further distinct properties of the Silesian economy are noticeable when contrasted with other historical regions.
Keywords: cities; trade; mining; agriculture; economic policy; demography; economic region